2005
DOI: 10.1021/jo050712d
|View full text |Cite
|
Sign up to set email alerts
|

Ti-Catalyzed Reactions of Hindered Isocyanates with Alcohols

Abstract: Highly hindered and sensitive isocyanates react with alcohols under mild catalysis by titanium tetra-t-butoxide to give high yields of the corresponding carbamates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 14 publications
1
37
0
2
Order By: Relevance
“…The termination reaction must be carried out at 08C, due to the reaction of methanol with the remaining monomer to give a carbamate product. 10 This alcohololysis reaction is greatly exothermic and is, probably, catalyzed by the titanium complex or HCl. A sudden rise in the temperature results in polymer degradation and formation of the undesired cyclotrimer, trihexyl isocyanurate.…”
Section: Hexyl Isocyanatementioning
confidence: 99%
“…The termination reaction must be carried out at 08C, due to the reaction of methanol with the remaining monomer to give a carbamate product. 10 This alcohololysis reaction is greatly exothermic and is, probably, catalyzed by the titanium complex or HCl. A sudden rise in the temperature results in polymer degradation and formation of the undesired cyclotrimer, trihexyl isocyanurate.…”
Section: Hexyl Isocyanatementioning
confidence: 99%
“…The transformation of 4 to a carbamate proved problematic because of the steric hindrance of the adjacent α‐carbon as well as the bulkiness of the alcohols used. Copper(I) chloride, titanium(IV) isopropoxide, and titanium(IV) tert ‐butoxide were tested as Lewis acids to assist in the conversion to the Fmoc‐protected amine; however, titanium(IV) tert ‐butoxide was found to give the best yield. From 5 , hydrolysis of the methyl ester yielded 6 , which was used in synthesis of the target peptides.…”
Section: Resultsmentioning
confidence: 99%
“…This reaction was originally developed for the titanium(IV) tert-butoxide mediated addition of alcohols to sterically hindered isocyanates to give the corresponding carbamates. [27] In this context it has been shown that tetrakis(dimethylamino)titanium(IV) also mediates the addition of dimethylamine to isocyanates to yield ureas. Treating isocyanates with a tertiary amine such as triethylamine as a catalyst, in 1,4-dioxane at room temperature, gives rise to the formation of the corresponding symmetrical ureas.…”
Section: Acyclic Unfunctionalized Ureasmentioning
confidence: 99%